SUI GENERIS DALAM PENGGUNAAN GEO STATIONARY ORBIT BERDASARKAN PRINSIP DAN HUKUM RUANG ANGKASA - Sartika Alamsyah, Dwi Putri; Suhartono, Slamet; Nasution, Krisnadi (Jurnal Hukum Bisnis Bonum Commune, 2020)
AbstractThe purpose of this research is to produce a review related to the exertion of Sui generis Regime in the utilization of Geo Stationary Orbit based on the principles of space law which are examined by comparison of laws and needs between developed and developing countries. This provision was made to provide legal substance related to technical matters and exertion related to the exploration of existing territories in space encompassing the Geo Stationary Orbit slot, and spacecraft  skimming. Developing countries strive to be determined "distinctive legal regime" (Sui Generis Regime) against the Geo Stationary Orbit (GSO) which is a specialty or specificity of existing international legal regimes or has previously been regulated in order not to become a stand-alone law. Research used a normative research using Normative Juridical methods namely by conducting an assessment related to legal aspects or the existence of regulations regarding space surrounding the responsibility of the problem. This is done to obtain data and to be able to analyze the sui generis regime on the exertion of geostationary orbits by Indonesia. The research is more concern related reviews special legal regime on the use of orbital slots which will experience challenges both in juridical and non-juridical terms, with the relationship between international law, this happened because there was no principium load, canon rule, and technical mechanism towards the 1967 space rules amendment. The uncertainty of these rules, especially in the utilization of Geo Stationary Orbit is used as a guideline for the need for the Sui Generis Regime as a regulation for the utilization of GSO which is inseparable from the principiums of space law. This is strengthened to provide benefits in terms of juridical and non-juridical aspects in the use of Geo Stationary Orbit. And aims to use space fairly and toward the interest of every humanity now or future.Keyword: geo stationary orbit; sui generis regime; the principle of spaceAbstrakTujuan [enelitian yaitu untuk menghasilkan ulasan terkait penggunaan Sui generis Regime dalam penggunaan Geo Stationary Orbit berdasarkan prinsip-prinsip hukum ruang angkasa yang dikaji dengan perbandingan hukum dan kebutuhan antara negara maju dengan negara berkembang. Ketentuan ini dibuat untuk memberikan subtansi hukum terkait hal-hal teknis dan penggunaan terkait ekplorasi wilayah yang ada di antariksa melingkupi slot Geo Stationary Orbit, serta peluncuran wahana antariksa. Negara-negara berkembang lebih mengupayakan agar dapat ditetapkannya “suatu rezim hukum khusus” (Sui Generis Regime) terhadap Geo Stationary Orbit (GSO) yang merupakan spesialisasi atau kekhususan dari rezim hukum internasional yang telah ada atau telah mengatur sebelumnya agar tidak menjadi hukum yang berdiri sendiri. Penelitian yang digunakan adalah penelitian normatif dengan menggunakan metode Yuridis Normatif yaitu dengan melakukan pengkajian terkait aspek hukum atau adanya regulasi tentang ruang angkasa melingkupi tanggung jawab permasalahan. Hal ini dilakukan untuk mendapatkan data dan agar dapat melakukan analisa sui generis regime terhadap pemanfaatan orbit geostationer oleh Indonesia. Penelitian lebih membahas ulasan terkait rezim hukum khusus berkaitan pemanfaatan  pada slot orbit akan mengalami tantangan baik dalam segi yuridis maupun non yuridis, dengan keterkaitan antara hukum internasional, hal ini terjadi karena tidak adanya muatan prinsip, aturan norma dan mekanisme teknis pada amandemen aturan luar angkasa 1967. Tidak tegasnya aturan tersebut terutama dalam penggunaan Geo Stationary Orbit dijadikan sebagai pedoman untuk perlunya Sui Generis Regime sebagai aturan penggunaan GSO yang tidak lepas dari prinsip-prinsip hukum ruang angkasa. Hal ini dikuatkan untuk memberikan keuntungan dari segi yuridis dan dari segi non yuridis dalam penggunaan Geo Stationary Orbit. Serta bertujuan untuk pemanfaatan ruang angkasa yang adil dan untuk kepentingan seluruh umat manusia sekarang ataupun masa yang akan datang.Kata kunci: geo stationary orbit; prinsip ruang angkasa; sui generis regime